Water volume changes and influencing factors in a typical lake on the Qinghai-Tibet Plateau: a case study of the basin of Lake Xiao Qaidam - Xinru Li; Shanlong Lu; Chun Fang; Harrison Odion Ikhumhen; Xinya Kuang; Yuan Guo; Xiaofeng Guo; Na Han; Meng Yang; Haihong Long; Jifang Ma; Yongshun Li; et al. (International Journal of Digital Earth)
In recent decades, significant changes have occurred in the river and lake systems of the Tibetan Plateau. This paper focuses on Lake Xiao Qaidam situated in the northeastern Qinghai-Tibet Plateau’s Qaidam Basin. By utilizing remote sensing and meteorological reanalysis data, as well as the Pettitt mutation point test and Mann-Kendall trend analysis, the study analyzes meteorological and hydrological data from 1987 to 2022 to explore the relationship between the lake system and regional climate factors. The research aims to uncover the mechanisms driving changes in the plateau's endorheic water systems and to inform the development of future management strategies. The findings reveal that rising temperature and increased glacier meltwater influx have caused significant increases in Lake Xiao Qaidam's surface area, volume, and water level, with the lake's area now reaching 120 km2. CMIP6 simulations suggest that these trends will likely persist, with the basin's increment in water volume projected to peak at approximately 1.6 km3 around 2033. This study confirms that climate change is a critical driver of hydrological changes in Lake Xiao Qaidam and its surrounding areas. These findings underscore the urgent need for enhanced water resource management.